Pengaruh Rasio Keuangan dan Good Corporate Governance terhadap Basic Earning Power dengan Variabel Moderasi Pertumbuhan Ekonomi - Nasihin, Ihsan; Dewi, Siska Komala (E-Jurnal Akuntansi; Vol 31 No 8 (2021)DO - 10.24843/EJA.2021.v31.i08.p17, 2021)
Companies have the main objective, namely to seek profit, but many factors influence the company to generate profits. The purpose of this study was to determine the factors that affect basic earning power. The research method in research is quantitative research, where the data used are secondary data. The population used in this research is in the form of the sub-Property and Real Estate manufacturing industries that have been listed on the IDX for the 2017-2019 period with a population of 74 companies. In the population, the method of illustration taking is the Non-Probability Sampling method. The results of this study indicate that the Working Capital Turnover, Long Term Debt to Equity Ratio, and Good corporate governance (GCG) have no effect on Basic Earning Power in the property and real estate sub-sector industries listed on the Indonesian stock exchange, so that economic growth cannot moderate financial ratios. Keywords: Financial Ratios; Good Corporate Governance; Basic Earning Power; Economic Growth.